Nucleotide metabolism-associated drug resistance gene NDUFA4L2 promotes colon cancer progression and 5-FU resistance - Hongxin HE; Shiyao ZHENG; Shangkun JIN; Weijie HUANG; Enhao WEI; Shen GUAN; Chunkang YANG (Scientific Reports)
Abstract Chemotherapy is an effective way to improve the prognosis of colorectal cancer patients, but patient resistance to chemotherapeutic agents is becoming a major obstacle to treatment. Nucleotide metabolism correlates with the progression of colorectal cancer and chemotherapy resistance, but the mechanisms involved need to be further investigated. We calculated the half-maximal inhibitory concentrations (IC50) of 5-Fluorouracil (5-FU) in colorectal cancer patients using the “oncopredict” package, screened nucleotide metabolism-related drug resistance genes, and constructed a risk score model. According to the Kaplan-Meier(KM) analysis, the overall survival (OS) and disease-free survival (PFS) of the high-risk group were significantly lower than those of the low-risk group. In addition, the nomogram we constructed had good performance in predicting OS in colon adenocarcinoma (COAD) patients. We validated NDUFA4L2 by cellular functionality experiments, animal tumorigenesis experiments and drug resistance experiments. It was demonstrated that NDUFA4L2 promoted the proliferation and migration of colon cancer cells, while the abnormal regulation of NDUFA4L2 affected the 5-FU resistance of colon cancer cells. In conclusion, we found that NDUFA4L2 promotes the progression and metastasis of colon cancer, as well as resistance to 5-FU chemotherapy.